Hubungan Pemberian Air Susu Ibu (ASI) Eksklusif Dengan Berat Badan Bayi Pada Hari Ke-10 Di Kota Denpasar Tahun 2018 - Ni Luh Eka Sapitri; Ni Nyoman Suindri (Poltekkes Kemenkes Denpasar, 2018)
The availability of exclusive breastmilk in Bali in 2016 is 48,4% and in Denpasar City is 43% under the national stage. This research is purposed to discover the relation between exclusive breastfeeding with babies weight in day 10 in Denpasar City in 2018. The research uses correlation-analytycal method with crossrectional layout. The sample used in this research is 39 babies in day 10 in Denpasar City who fulfill the inclusion criteria. The sampling technique used is probablity sampling with consecutive sampling method from May until June 2018. The analytycal technique is Chi Square test. The result of this research shows that the babies who do not get any breastfeeding exclusively don’t get their weight back in day 10 (9 babies/64,3%). Meanwhile, the babies who got their exclusive breastmilk and got their weight backin day 10 are 19 babies (76%). The result of Chi Square test is indicated from the probability value p=0,013 which means there is the relationship between exclusive breastfeeding with babies weight in the day 10 in Denpasar City in 2018, so there is a need to give a socialization regarding the gives of exclusive breastmilk to gain the weight for the babies back.